Measuring writing : recent insights into theory, methodology and practices - Steendam, Elke van; Tillema, Marion; Rijlaarsdam, Gert; Bergh, Huub van den (Studies in writing., 2012)
Provides an overview of theory, methodology and practices in the assessment of writing. This title discusses whether varying definitions and varying operationalizations of writing ability are needed in various contexts, such as formative assessments versus summative assessments, different tasks, different genres, and different languages.